Biophysical characterization of the first ultra-cyclist in the world to break the 1,000 km barrier in 24-h non-stop road cycling: A case report - Knechtle, Beat; Forte, Pedro; Weiss, Katja; Cuk, Ivan; Nikolaidis, Pantelis T.; Sousa, Caio Victor; Andrade, Marilia Santos; Thuany, Mabliny (Frontiers in Cardiovascular Medicine, 2022)
A plethora of factors determine elite cycling performance. Those include training characteristics, pacing strategy, aerodynamics, nutritional habits, psychological traits, physical fitness level, body mass composition, and contextual features; even the slightest changes in any of these factors can be associated with performance improvement or deterioration. The aim of the present case report is to compare the performances of the same ultra-cyclist in achieving two world records (WR) in 24 h cycling. We have analyzed and compared the distance covered and speed for each WR. The 24 h period was split into four-time intervals (0–6 h; > 6–12 h; > 12–18 h; > 18–24 h), and we compared the differences in the distance covered and speed between the two WRs. For both WRs, a strong negative correlation between distance and speed was confirmed (r = –0.85; r = –0.89, for old and new WR, respectively). Differences in speed (km/h) were shown between the two WRs, with the most significant differences in 12–18 h (Δ = 6.50 km/h). For the covered distance in each block, the most significant differences were observed in the last part of the cycling (Δ = 38.54 km). The cyclist effective surface area (ACd) was 0.25 m2 less and 20% more drag in the new WR. Additionally, the mechanical power was 8%, the power to overcome drag was 31%, and the power-weight ratio was 8% higher in the new WR. The mechanical efficiency of the cyclist was 1% higher in the new WR. Finally, the heart rate (HR) presented significant differences for the first 6 h (Old WR: 145.80 ± 5.88 bpm; New WR: 139.45 ± 5.82 bpm) and between the 12 and 18 h time interval (Old WR: 133.19 ± 3.53 bpm; New WR: 137.63 ± 2.80 bpm). The marginal gains concept can explain the performance improvement in the new WR, given that the athlete made some improvements in technical specifications after the old WR.